Green approach for an eco-compatible consolidation of the Agrigento biocalcarenites surface. (20th October 2018) - Daniele, V.; Taglieri, G.; Macera, L.; Rosatelli, G.; Otero, J.; Charola, A.E.
Highlights: Green and compatible conservative treatments on Agrigento biocalcarenites. The treatments are performed by a new no-commercial aqueous nanolime suspension. Nanolime is produced by a single-step, time/energy-saving and scalable route. Petrographic and chemico-physical analyses of biocalcarenites are performed. The treatment effectiveness is evaluated following standard procedures. Abstract: In this paper, we investigate a conservation treatment on different kinds of Agrigento's biocalcarenites, introducing a new non-commercial aqueous nanolime suspension for compatible and eco-friendly extensive applications. This nanolime, here tested for the first time, can be considered a green treatment for both the environment and the health of the conservator. Petrographic, chemico-physical and mechanical investigations of the different biocalcarenites were carried out before and after treatment application. This new nanolime yielded a very promising consolidation effectiveness for all the biocalcarenites, increasing the superficial cohesion and the drilling resistance without significantly altering the stone porosity or the aesthetical features.